Enhancing students’ understanding on job hunting skills through board game (Southeast Asian Journal of Technology and Science, 2023)
To date, issue on graduate employability has been seriously discussed by public. Many factors have been associated with their failure to obtain job upon graduation. One of the factors that usually being highlight is the lack of soft skill among them. They seem unable to acquire important skills such as communication, problem solving, teamwork or leadership skills which is important criteria that the employer looking for. Realising this issue, this game board has been developed and being used during lecture to attract students’ interest and to add to the new teaching methods. Improving or coming out with new teaching method is important to suit with the needs of this generation of students. To date, game-based learning approach is suitable to be used because students can master problem solving skills directly or indirectly during the game session. The idea to developed this board game came when saw the students struggled while doing mock interviews due to lack of understanding and practice, hence cause them to get lower score in the assessment. This teaching aids is specifically designed to enhance students’ understanding of jobhunting skills that consist of job advertisement, resume and interview. This teaching aids is suitable for teaching and learning because it can increase students' understanding, as well as to inculcate students’ interest towards the subject matter, through rapid learning and revision while playing. Due to limited job hunting board games in the market, The Job Hunters is very suitable to be promoted as one of the learning tools, especially in the field of job hunting and communicative English.